Past perfect ebook A novel. - Steel, Danielle (2017)
NEW YORK TIMES BESTSELLER • Past Perfect is a spellbinding story of two families living a hundred years apart who come together in time in a startling moment, opening the door to rare friendship and major events in early-twentieth-century history. Sybil and Blake Gregory have established a predictable, well-ordered Manhattan life—she as a cutting-edge design authority and museum consultant, he in high-tech investments—raising their teenagers Andrew and Caroline and six-year-old Charlie. But everything changes when Blake is offered a dream job he can’t resist as CEO of a start-up in San Francisco. He accepts it without consulting his wife and buys a magnificent, irresistibly underpriced historic Pacific Heights mansion as their new home. The past and present suddenly collide for them in the elegant mansion filled with tender memories and haunting portraits when an earthquake shocks them the night they arrive. The original inhabitants appear for a few brief minutes. In the ensuing days, the Gregorys meet the large and lively family who lived there a century ago: distinguished Bertrand Butterfield and his gracious wife Gwyneth, their sons Josiah and little Magnus, daughters Bettina and Lucy, formidable Scottish matriarch Augusta and her eccentric brother Angus. All long since dead. All very much alive in spirit—and visible to the Gregorys and no one else. The two families are delighted to share elegant dinners and warm friendship. They have much to teach each other, as the Gregorys watch the past unfold while living their own modern-day lives. Within these enchanted rooms, it is at once 1917 and a century later, where the Gregorys gratefully realize they have been given a perfect gift—beloved friends and the wisdom to shape their own future with grace from a fascinating past. Past Perfect is Danielle Steel at her bewitching best, a novel for the ages.